Melliferous flora of Chernyaev forest and melissopaly-nology analysis of honey products of a school apiary - A. A. Vakhrushev; V. P. Buravleva (Аграрная наука Евро-Северо-Востока, 2018)
The article presents an analysis of the bee forage in Chernyaev forest, Perm. The investigated phytocenosis is represented by 59 species of honey plants belonging to 24 families and 49 genera. According to the results of geobotanical assessment, the largest group of honey plants in Chernyaev forest includes nectar- pollen plants - 86.4%, the vast majority of bee plant species belongs to the Rosaceae family, they account for 21.6% of the total. According to the resource role, the identified taxons are represented by two groups. The largest group consists of nectar-pollen bearing plants (77%), the group of pollen plants includes 4 taxons (23%).